Story, song, and ceremony: shaping dispositions in Japanese elementary schools during Taisho and early Showa. Issue 1 (2nd January 2016) - Cave, Peter
Abstract: Japanese elementary schools of the Taisho and early Showa periods sought to shape children into 'good Japanese' through an imaginary communicated in a range of media and activities, intended to form children's dispositions through a combination of discipline and attraction. Ceremonies for the reading of the Imperial Rescript on Education, held on four major annual holidays, disciplined children into awe of the Emperor. In contrast, stories of exemplary heroes were communicated in forms aimed at inspiring children and moving their emotions, from textbook stories and songs, to plays at gakugeikai (school revues). Such heroes ranged from medieval imperial loyalists such as Kusunoki Masashige and his family, to figures from the Russo-Japanese War such as Nogi Maresuke and Hirose Takeo. Education movements of the Taisho period, pedagogically progressive in their focus on whole-person education, encouraging drama, singing, and other artistic activities, could serve nationalist purposes by making such heroes' stories more emotionally involving.